Climate risk and value chain vulnerability assessment: Stakeholder mapping, hazard hotspot identification, and sensitivity analysis for climate-resilient interventions in Mozambique - Gamoyo, Majambo; Koech, Grace; Chilambe, Pedro; Osiemo, Jamleck; Binge, Brenda (2025)
This report presents a Rapid Climate Risk Analysis for Mozambique’s Nampula and Zambezia regions, with the overarching aim of informing the development of an evidence-based, context-specific adaptation toolkit to strengthen climate resilience in key agricultural value chains. The regions face heightened vulnerability to climate change due to rising temperatures, erratic rainfall, and increased frequency of extreme weather events such as droughts, floods, and tropical cyclones. These climatic stressors significantly threaten agricultural productivity, rural livelihoods, and socio-economic stability. Utilizing historical data and climate projections under SSP245 and SSP585 scenarios, the analysis identifies critical vulnerabilities and hazard hotspots, particularly areas exposed to compounded risks of heat stress and drought. The report emphasizes the need for tailored adaptation strategies to mitigate these risks and enhance resilience, while also contributing to Mozambique’s national adaptation and sustainable development objectives. Key components of the report include stakeholder mapping, climate trend analysis, and recommendations for targeted resilience interventions.